2015
DOI: 10.1016/j.bbrep.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

IL-38: A new factor in rheumatoid arthritis

Abstract: The newly characterized cytokine IL-38 (IL-1F10) belongs to the IL-1 family of cytokines. Previous work has demonstrated that IL-38 inhibited Candida albicans-induced IL-17 production from peripheral blood mononuclear cells. However, it is still unclear whether IL-38 is an inflammatory or an anti-inflammatory cytokine. We generated anti-human IL-38 monoclonal antibodies in order to perform immunohistochemical staining and an enzyme-linked immunosorbent assay. While human recombinant IL-38 protein was not cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 21 publications
4
55
0
2
Order By: Relevance
“…Previously, it has been shown that IL-38 deficient mice exhibit more severe STIA than wild type mice 14. Our present study expands these results and demonstrates for the first time that AAV-mediated IL-38 overexpression exerted moderate but significant anti-inflammatory effects in mice with CIA or STIA.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Previously, it has been shown that IL-38 deficient mice exhibit more severe STIA than wild type mice 14. Our present study expands these results and demonstrates for the first time that AAV-mediated IL-38 overexpression exerted moderate but significant anti-inflammatory effects in mice with CIA or STIA.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, patients with systemic lupus erythematosus, chronic hepatitis B, myocardial infarction or childhood asthma have higher levels of serum IL-38 than control populations 7–13. IL-38 levels are also increased in the synovial membrane and sera from patients with RA compared with healthy controls 13 14. We have previously shown that IL-38 mRNA levels are enhanced in synovial membranes of patients with RA and in colons of patients with Crohn's disease.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Further analysis is required to test this hypothesis. Takenaka et al investigated AIA in IL-38 KO and observed greater disease severity, accompanied by higher IL-1β and IL-6 gene expression in the joints compared to control mice [47]. Recently, Boutet et al demonstrated that adeno-associated virus-mediated IL-38 overexpression exerted moderate but significant anti-inflammatory effects in CIA and K/BxN serum transfer-induced arthritis (STIA) [48].…”
Section: Il-36 and Il-38mentioning
confidence: 99%
“…Of note, IL-38 overexpression did not induce the production of other anti-inflammatory cytokines, but reduced significantly IL-10 expression. IL-38 levels are increased in the synovial membrane and sera from patients with RA compared with healthy controls [47,49] IL-38 is expressed by keratinocytes, synovial fibroblast from patients with RA, as well as by human monocytes and type I macrophages polarized in vitro [41].…”
Section: Il-36 and Il-38mentioning
confidence: 99%